1995
DOI: 10.1109/23.489237
|View full text |Cite
|
Sign up to set email alerts
|

Simulation aided hardening of N-channel power MOSFETs to prevent single event burnout

Abstract: 2D MEDIC1 simulator is used to investigate hardening solutions to single-event burnout (SEB). SEB parametric dependencies such as carrier lifetime reduction, base enlargement, and emitter doping decrease have been verified and a p' plug modification approach for SEB hardening of power MOSFETs is validated with simulations on actual device structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…The simulation data on SEB in our paper are in agreement with the theoretical analysis and other authors' research data [7]- [10]. In this paper, we mainly focus on the beneficial physical effects for the radiation immunity of the new structure compared with standard power UMOSFET.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…The simulation data on SEB in our paper are in agreement with the theoretical analysis and other authors' research data [7]- [10]. In this paper, we mainly focus on the beneficial physical effects for the radiation immunity of the new structure compared with standard power UMOSFET.…”
Section: Introductionsupporting
confidence: 87%
“…It has been proved that p+ plug enlargement is an effective way to improve the SEB performance [7]. There are also many other parameters which can affect the occurrence of SEB such as carrier lifetime reduction and emitter doping decrease [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is located in the intercellular region right next to the channel. This position was found by different experimental studies and numerical simulations to be among the most sensitive positions to SEB [9], [10], [14]- [16]. In addition, the choice of this position for the charge generation allows one to simulate only half of a VDMOS cell, since the influence of the adjacent half cell can be considered to be negligible.…”
Section: Simulation Tool and Test Vehicle Descriptionsmentioning
confidence: 97%
“…It is demonstrated that the p+ plug enlargement can make the device less sensitive to SEB [5]- [7]. Simulation and experimental results confirm that the addition of a buffer layer does indeed improve the device's SEB threshold voltage, thus, improving the device's SEB performance [8].…”
Section: Introductionmentioning
confidence: 81%
“…The aim of this paper is to harden the structure of the power UMOSFETs with design modifications [5]. The solutions simply modify the geometry of the p + plug, maintaining though the initial functionality of the device (it is verified that BV, V th , R DSon , and I-V characteristics are unchanged).…”
Section: B Modification Of the P + Plug Geometrymentioning
confidence: 99%